Arctic Governance Through Conferencing Actors, Agendas and Arenas - Steinveg, Beate (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book examines the functions of conferences within Arctic governance, as a third dimension between sovereign states and formalized cooperative arrangements. It analyzes conferences against the background of three main empirical topics. Firstly, the functions of conferences for different actor groups, both Arctic rights holders and emerging non-Arctic state actors claiming stakeholder status. From this, the book also analyzes how conferences contribute to altering the actor composition of Arctic governance as a whole. Secondly, conferences as agenda setting arenas - whether conference activities can contribute to influencing the broader agenda in the region, and conferences as arenas for agenda setting - whether participants can bring with them topics that are picked up and brought into other processes. Thirdly, the book considers the space for conferences within broader governance architectures, as links between units in the regime complex. The book further presents an in-depth case study of the two largest conferences on Arctic issues: the Arctic Frontiers and Arctic Circle Assembly. It illustrates the diverse functions conferences can have for elements within a broader governance system, beyond serving as meeting places and networking arenas. Therefore, it is a must-read for researchers, students, and policy-makers interested in a better understanding of Arctic governance in particular, and International Relations in general.
Chapter 1. Introduction -- Chapter 2. Arctic Governance: Actors, Processes, and Structures -- Chapter 3. Arctic Frontiers and Arctic Circle Assembly -- Chapter 4. Actors in the Arctic Conference Sphere -- Chapter 5. Conferences as Agenda Setting Arenas -- Chapter 6. Conferences within the Arctic Governance Architecture -- Chapter 7. Conclusions: Governance by Conference.
Keywords: International organization; Diplomacy; Security, International; Political science; Public policy; International Organization; Diplomacy; International Security Studies; Governance and Government; Agenda Setting